2011
DOI: 10.1038/onc.2011.123
|View full text |Cite
|
Sign up to set email alerts
|

MSX2 is an oncogenic downstream target of activated WNT signaling in ovarian endometrioid adenocarcinoma

Abstract: Ovarian endometrioid adenocarcinomas (OEAs) frequently exhibit constitutive activation of canonical WNT signaling, usually as a result of oncogenic mutations that stabilize and dysregulate the b-catenin protein. In previous work, we used microarray-based methods to compare gene expression in OEAs with and without dysregulated b-catenin as a strategy for identifying novel b-catenin/TCF target genes with important roles in ovarian cancer pathogenesis. Among the genes highlighted by the microarray studies was MSX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…In particular, ZEB1 expression was reported to be closely linked with EMT in various cancer cells, including breast cancer. Increasing studies have demonstrated that the Wnt is the major signaling pathway that involved in EMT [26,27]. It is a critical developmental pathway involved in differentiation, migration, invasion and adhesion; these cellular processes are key components of tumorigenesis and metastasis [28].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ZEB1 expression was reported to be closely linked with EMT in various cancer cells, including breast cancer. Increasing studies have demonstrated that the Wnt is the major signaling pathway that involved in EMT [26,27]. It is a critical developmental pathway involved in differentiation, migration, invasion and adhesion; these cellular processes are key components of tumorigenesis and metastasis [28].…”
Section: Discussionmentioning
confidence: 99%
“…S5B in the supplemental material). Dlx3 and Msx2 are transcription factors required for amelogenesis (47) and regulated by the Wnt/␤-catenin pathway (48,49). ISH of serial sections indicated that the expression of these two factors and Amelx was significantly downregulated in Ctnnb1-negative epithelia in both molars and incisors ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, both DLX4 and DLX5 induce c-Myc expression (Xu and Testa 2009;Trinh et al, 2011). On the other hand, MSX1 induces expression of growth arrest genes such as GADD153 and inhibits proliferation of ovarian cancer cells (Park et al, 2001), whereas MSX2 promotes ovarian cancer growth (Zhai et al, 2011). As discussed earlier, diversity in amino acid residues in the homeodomain and other motifs of family members gives rise to different DNA-binding specificities and can result in different phenotypes.…”
Section: Sustained Proliferative Signalingmentioning
confidence: 99%
“…There is considerable evidence that patterning of the reproductive tract is controlled by a regulatory network of distinct sets of Wnts and homeobox genes (Kobayashi & Behringer, 2003). MSX2 is a transcriptional target of -catenin/TCF and MSX2 expression is increased in endometrioid ovarian carcinomas with deregulated -catenin (Zhai et al, 2011). Expression of AbdB HOX genes in the endometrium is also tightly regulated by estrogen and progesterone .…”
Section: Developmental Signalsmentioning
confidence: 99%